The Influence of Twitter Social Media Usage on Student Behavior: A Case Study of 'Alone Together' - Syalaisha Nabila; Ciello Alvanda Laurend; Eliya Kurniawati (Universitas Negeri Malang, 2024)
Social media has become an integral part of teenagers' lives in this digital era. In this context, this study aims to measure the extent of the influence of social media on the behavior of teenagers who often experience the phenomenon of